Using Picture in Writing Paragraph the Eleventh grade Students of SMK SPP. S.t Paulus Makale - matius tandi kombong (Teaching English as a Foreign Language Overseas Journal, 2016)
The aim of this research is to find out whether the use of picture in writingparagraph improves the students’ writing ability. This research used experimentalmethod. The population was the eleventh grade students of SMK. SPP. St. PaulusMakale, academic year 2015/2016, there were 62 students as population. Thesample of the research was the students of the XI-I. The writer used the clusterrandom sampling method, it means the researcher use one class as sample in thisresearch namely the eighth class one, and there were 31students as sample. Thedata collected through written pre-test and post-test. The data was analyzed byusing the five components of writing, namely: content, organization, vocabulary,language use, and mechanic The result of comparison between students’ score inpre-test and post-test indicated that there was a significant differenceimprovement of writing ability between the students who were taught by pictureand those who were not. The mean score of pre-test was 53,41 and the mean scoreof post-test was 58,25. It means that the means score of post-test was improved4,84 than pre-test. The increasing of the mean score of post-test indicates thatteaching writing with using picture improves the students’ writing ability at TheEleventh Grade Students of SMK SPP. S.T PAULUS MAKALE.